PENGARUH PENATALAKSANAAN FISIOTERAPI PADA ANAK KONDISI AUTISME DENGAN MODALITAS PLAY EXERCISE (PERCEPTUAL MOTOR PROGRAM) DAN HIDROTERAPI (BALANCE AND COORDINATION) DI YPAC SURAKARTA - Tiara Arifadhi; Nur Susanti (LPPM Universitas Pekalongan, 2019)
Autism is a condition of clear abnormalities and developmental disorders in social interactions, communication, and obvious limitations in activity and interest. Autism physiotherapy itself is a disorder of attention or behavior, sensory disorders, primitive reflex disorders, muscle strength disorders and functional activity disorders standing and walking. In this case, the intervention technology chosen to overcome the above problems using Play Exercise (Perceptual motor program) and Hydrotherapy (Balance and Coordination). This research was conducted at YPAC Surakarta with descriptive analytic research design. The subjects of this study were patients with autism condition will be given physiotherapy intervention by Play Exercise method (Perceptual motor program) and Hydrotherapy (Balance and Coordination). Data collection method of data analysis using heteroanamnesis interview method The research instrument consists of DSM-IV examination,primitive reflex examination, muscle strength examination and functional activity examination The research design used was case study design. Based on the therapy that has been done, the following results were obtained: Decrease of attention / behavioral disorder in the field of social interaction, T4 = 3 symptoms; sensory increase in auditory, propioseptive, and vestibular T4 = 3, 2, 2; decreased primitive reflexes of supine, prone and sitting equlibrium reaction; increased muscle strength of lower limbs and trunk; Increased functional activity is up and running.